Common variable immunodeficiency presenting as sarcoidosis in a 9‐year‐old child. (19th December 2019) - Maccora, Ilaria; Marrani, Edoardo; Ricci, Silvia; Azzari, Chiara; Simonini, Gabriele; Cimaz, Rolando; Giani, Teresa
Abstract: Background: Granulomatous diseases are a heterogeneous group of conditions characterized by an inflammatory infiltrate with a core of macrophages, epithelioid, giant cells and a corona of fibroblasts and lymphocytes. They are associated with a wide range of disorders such as mycobacterial and fungal infections, neoplasms, immunodeficiencies and systemic inflammatory disorders as sarcoidosis. Case report: We report the case of a previously healthy 9‐year‐old male child who presented with persistent cough, diffuse lymphadenopathy, enlargement of liver and spleen and protracted fever. Anemia, lymphopenia and reduced platelet count was reported, with an increase of inflammatory markers. High levels of Angiotensin‐converting enzyme and chitotriosidases were noted. A PET‐CT scan showed increased uptake of 18 F‐FDG glucose in multiple lymph nodes in thorax and abdomen and in the spleen. Biopsy of inguinal and bronchial nodes showed nodal granulomatous inflammation. The child was diagnosed with sarcoidosis and treated with corticosteroids with only transient efficacy. Further tests reported panhypogammaglobulinaemia and a reduced pool of B‐memory lymphocytes. Thus, the diagnosis was revised to common variable immunodeficiency (CVID). Conclusion: Common variable immunodeficiency is a heterogeneous condition with a highly variable clinical phenotype and a strong association with autoimmune disorders. The presence of noncaseating granuloma and pulmonary lesions, along with extrapulmonary features required a step by step approach to differentiate between CVID and sarcoidosis. This enables early introduction of immunoglobulin replacement therapy and decreases the morbidity and mortality of CVID.